Engaging Australian Aboriginal narratives to challenge attitudes and create empathy in health care: a methodological perspective. Issue 1 (December 2016) - Wain, Toni; Sim, Moira; Bessarab, Dawn; Mak, Donna; Hayward, Colleen; Rudd, Cobie
Abstract Background Unconscious bias and negative attitudes towards minority groups have detrimental effects on the way health care is, or is not, provided to these groups. Recognition of racist attitudes and behaviours as well as understanding clients' experiences of health and health care are pivotal to developing better health care strategies to positively impact on the quality and safety of care provided to Indigenous people. Indigenous research demands inclusive research processes and the use of culturally appropriate methodologies. This paper presents a methodological account of collecting narratives which accurately and respectfully reflect Aboriginal Australians' experiences with health care in Western Australia. The purpose of these narratives is to provide health students and professionals with an opportunity to 'walk-in the shoes' of Aboriginal people where face-to-face interaction is not feasible. Methods With the incorporation of Indigenous peoples' voices being an important link in cultural safety, the project was led by an Indigenous Reference group, who encouraged active participation of Aboriginal people in all areas of the project. Using a phenomenological approach and guided by the Indigenous Reference group, yarning data collection was implemented to collect stories focusing on Aboriginal people's experiences with health care services. An open-access, on-line website was established to host education resources developed from these "yarns". Results Yarning provided a rich source of information on personal experiences and encouraged the story provider to recognise their facilitative role in the research process. While the methodology used in this project was lengthy and labour-intensive it afforded a respectful manner for story collection and highlighted several innate flaws when Western methods are applied to an Indigenous context. Conclusion Engagement of an Indigenous Reference Group was pivotal to designing an appropriate methodology that incorporated the voices of Aboriginal people in a multimedia resource of Aboriginal narratives. However further research is warranted to understand how the resources are being used and integrated into curricula, and their impact on students and health care outcomes.